Neuroendocrine Tumors (NETs) of the Minor Papilla/Ampulla: Analysis of 16 Cases Underlines Homology With Major Ampulla NETs and Differences From Extra-Ampullary Duodenal NETs. (June 2019) - Vanoli, Alessandro; Albarello, Luca; Uncini, Stefania; Fassan, Matteo; Grillo, Federica; Di Sabatino, Antonio; Martino, Michele; Pasquali, Claudio; Milanetto, Anna C.; Falconi, Massimo; Partelli, Stefano; Doglioni, Claudio; et al.
Abstract : Neuroendocrine tumors (NETs) of the minor papilla/ampulla (MIPA) are rare and poorly studied. Only individual case reports and no comprehensive analysis are available from the literature. We collected 16 MIPA NETs and investigated their clinicopathologic and immunohistochemical features, including markers such as somatostatin, pancreatic polypeptide, gastrin, serotonin, MUC1, cytokeratin 7, and somatostatin receptors type 2A and 5. The median age at diagnosis was 57.5 years, and the female-to-male ratio was 2.2:1. The median NET size was 1.45 cm, and most (94%) were low-grade (G1) tumors. Similarly to what was observed in the major ampulla, 3 histotypes were found: (i) ampullary-type somatostatin-producing tumors (ASTs, 10 cases), characterized by somatostatin expression in most tumor cells, focal-to-extensive tubulo-acinar structures, often with psammoma bodies, MUC1 reactivity, and no or rare membranous reactivity for somatostatin receptor type 2A; (ii) gangliocytic paragangliomas (3 cases), characterized by the coexistence of 3 tumor cell types: epithelioid, often reactive for pancreatic polypeptide, ganglion-like cells, and S100 reactive sustentacular/stromal cells; and (iii) ordinary nonfunctioning NETs (3 cases), resembling those more commonly observed in the extra-ampullary duodenum. Comparable histotypes could also be recognized among the 30 MIPA NETs from the literature. No NET-related patient death among MIPA cases was observed during a median follow-up of 38 months; however, MIPA ASTs showed lymph node metastases and invasion of the duodenal muscularis propria or beyond in 44% and 40% of cases, respectively. In conclusion, MIPA NETs closely resemble tumors arising in the major ampulla, with predominance of ASTs.